2021
DOI: 10.1016/j.jbc.2021.101045
|View full text |Cite
|
Sign up to set email alerts
|

UGT86C11 is a novel plant UDP-glycosyltransferase involved in labdane diterpene biosynthesis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 79 publications
(143 reference statements)
0
6
0
Order By: Relevance
“…This result conforms to the published values for other UGTs, with their optimal temperature range between 30-40 °C. 47–50…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result conforms to the published values for other UGTs, with their optimal temperature range between 30-40 °C. 47–50…”
Section: Resultsmentioning
confidence: 99%
“…This result conforms to the published values for other UGTs, with their optimal temperature range between 30-40 °C. [47][48][49][50] We further investigated the thermostability of LbUGT72B10 (Fig. 5C).…”
Section: Biochemical and Kinetic Characterization Of Lbugt72b10mentioning
confidence: 99%
“…Sun et al (2019)functionally characterized recombinant UGT73AU1, UGT71, UGT76, UGT85, and UGT88 from A. paniculata and reported that ApUGT37AUI could convert andrograpanin to neoandrographolide [37]. However, an extensive functional characterization of 23 UGTs from A. paniculata revealed that UGT86CII could be the most probable enzyme, and it showed relatively higher catalytic activity than UGT73AUI ( Srivastava et al, 2021 ). A. alata transcriptome contained 103 transcripts coding for 21 UGTs, including a full-length gene for UGT73AUI (AaUGT73AUI) and a partial gene for UGT86CII (AaUGT86CII).…”
Section: Discussionmentioning
confidence: 99%
“…The Andrographis genus contains 29 species, including A. paniculata, A. alata, A. gracilis, A. affinis, A. longipedunculata , A. elongata , and A. macrobotrys ( Gnanasekaran and Murthy, 2015 ). Genes coding for NADPH: cytochrome P450 reductase, ent-copalyl diphosphate synthase, geranylgeranyl pyrophosphate synthases (GGPPS), and UDP-glucotransferase (UGT) were cloned from A. paniculata and functionally characterized ( Lin et al, 2017 , Misra et al, 2015 , Wang et al, 2019 , Srivastava et al, 2021 ). Chromosome-level genome sequence and transcriptome data are also available for A. paniculata ( Liang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…ThActin was selected as the reference gene for normalizing the expression of the target gene. Relative transcript expression was determined using the 2 -ΔΔC T method (Srivastava et al, 2021). Triplicate reactions were conducted for each cDNA sample to ensure data correctness.…”
Section: Fungal Culture Growth Rna Extraction and Qrt-pcr Analysismentioning
confidence: 99%